The Effect of Realistic Mathematics Education on Fourth Graders' Problem Posing/Problem-solving Skills and Academic Achievement - Kübra AYTEKİN-USKUN; Osman ÇİL; Okan KUZU (Anı Publishing, 2021)
This study investigated the effect of the Realistic Mathematics Education (RME) approach on fourth-grade students' achievement and problem posing and problem-solving skills based on four basic operations. "Academic Achievement Test towards Four Basic Operations" was administered to a total of 70 students. Case study model was used in the qualitative part of the research designed with a mixed model, and the obtained data were analyzed by content analysis. The quantitative part of the study was carried out using a quasi-experimental pretest-posttest design with the control group. After the 17-week experimental process, a significant difference was found in experimental group students' academic achievements and problem posing and problem-solving skills using four basic operations. Students who received instruction based on the RME approach comprehended the problem statements better, created more meaningful problems and developed their ability to select the appropriate data and the operation. Extending the classroom use of the RME approach will effectively improve students' problem posing and solving skills and increase student achievement in international exams.